Um estudo sobre estratégias de recursos humanos de uma empresa terceirizada do setor de telecomunicações - Araujo, Jucelia Laurindo de (2016)
The objective of the research conducted for this dissertation was to analyze the human resources (HR) strategies and policies adopted in an outsourced telecom company, considering its strategic importance in the economic and globalized scenario. Specific objectives were analyzing the telecom industry in Brazil and the service relations between outsourced and contracting companies. In order to make carrying out the research possible, an investigation was conducted of aspects related to HR strategies and policies, and of outsourcing from a strategic and critical viewpoint; also carried out were analyses of the telecom industry and its strategies of action, and, finally, of the case of an outsourced telecom company. The methodology adopted consisted of a case study involving an exploratory approach, which was qualitative by nature, by means of three sources of evidence: documentation, files on record and participant observation. The subject of the investigation selected was an outsourced company named Alfa, which is engaged in providing services for major telecom operators here in Brazil. The results obtained indicated that it is possible to obtain good human resources practices by improving the outsourcing strategies and also reducing the negative effects, viewed as a precarious factor in terms of working arrangements